A case of perinevic salt-dependent aquagenic urticaria in a 9-year-old boy. - Greenspoon, T.; Eshtiaghi, P.; Weinstein, M. (European Journal of Pediatric Dermatology, 2020)
Aquagenic urticaria (AU) is a chronic inducible urticaria characterized by rapid development of hives following skin exposure to water. Lesions are 1-3 mm, perifollicular, pruritic wheals that spontaneously resolve within 30-60 minutes. Systemic symptoms are possible (1, 2). Salt-dependent aquagenic urticaria (SDAU) is a rare subtype of AU after contact with salt water only. It affects primarily females with a predilection for the inferior facial contours and neck (4). Since its first description in 2001, SDAU has been reported in 9 adult cases (2, 3, 6), all in females and almost all localized to the face and neck (Table 1). The first two pediatric cases of SDAU were recently reported in the literature, of two non-atopic girls, ages 7- and 9-years-old, who developed urticaria in response to sea bathing, on the face and neck, with positive response to 3.5% NaCl testing (4). In both children, reactions were subsequently avoided by pre-treatment with a second-generation H1 antihistamine at standard doses (4). […]